A Complex Coronary Artery Fistula as a Potential Cause of Sudden Intraoperative Hemodynamic Compromise: A Case Report. (December 2020) - Deana, Cristian; Baron, Daniele; Barbariol, Federico; Negri, Katerina; Vecil, Marco; Vetrugno, Luigi; Bove, Tiziana; Monte, Amato De
A patient with coronary artery fistula should be considered as high risk for intraoperative hemodynamic decompensation. In this article, we report the case of a 70-year-old man affected by a complex congenital coronary artery fistula defect. The patient underwent general anesthesia for spine surgery with permissive hypotension. The development of sudden intraoperative tachyarrhythmia with hemodynamic instability required immediate resuscitation and interruption of surgery. The claim advanced is that in patients with a coronary artery fistula permissive hypotension might be considered an option only if strictly necessary and real-time cardiac monitoring including transesophageal echocardiography is available to immediately detect and treat acute cardiac impairment.